Ceasefire monitoring under fire: The OSCE, technology, and the 2022 war in Ukraine. Issue 5 (16th August 2022) - Verjee, Aly
Abstract: This Policy Insight discusses what was the world's largest dedicated third‐party ceasefire monitoring operation, the Special Monitoring Mission (SMM), which, until the Russian invasion in early 2022, oversaw a ceasefire in Ukraine. Although it may now seem obvious to conclude that the SMM failed to deter conflict escalation, this once‐heralded, 'model' mission provides insights for the design and implementation of other ceasefire monitoring efforts. This Policy Insight argues that the limitations and differing interpretations of the SMM's mandate, an inability to attribute responsibility for violations, and a failure to act in response to violations substantially weakened the practice of ceasefire monitoring in Ukraine. Still, important lessons can be identified for future monitoring work, whether in Ukraine or elsewhere, including agreeing on the mechanisms for consequences when violations occur, better understanding the limitations of remote sensing technology in monitoring, and establishing more robust planning for mission suspension, evacuation, and termination.